Structural equation model of factors affecting Thailand's commercial bank branch expansion - Meesrijan, Sittichai; Fongsuwan, Wanno (My University, 2015)
As a result of the 1997 Asian financial crisis, many Thai banks were forced to close. As a result, the Thai financial system and commercial banks required an infusion of capital which in many instances was of foreign nature resulting in foreign investors becoming shareholders in the banks. As a result of t he global financial crisis in 2008, the Bank of Thailand issued 7 directives concerning Basel III capital ratios of local and foreign banks operating in the Kingdom. Also in 2013, major revisions were again released by the Bank of Thailand for the licensing of new foreign commercial banks wishing to operate in the Kingdom. In this environment of dynamic global and regional change, the researchers undertook this study using both quantitative and qualitative research methods from a survey population of commercial bank executives. It was discovered that bank branch expansion was related to both corporate leadership and economic factors. Economic factors also influence leadership in determining strategic plans as well as teamwork in the ability to continue opening new branches. It was noted however that branch cost factors have minor influence on the opening of t he bank because the expectation is that with the increased customers, new customers' fees and charges offset the additional operational overhead. The research noted that marketing with niche technologies such as telephone and Internet affected building relationships with customers and was a relationship marketing tool.
Keywords: Banking; Branch expansion; Cost; Economic factors; Leadership